2012
DOI: 10.2494/photopolymer.25.271
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Properties and Charge Dynamics in Nanophase-Separated F8T2/PCBM Blend Films

Abstract: We studied organic photovoltaics (OPVs) in bulk-heterojunction cells (BHJ) based on a liquid-crystalline fluorine copolymer (F8T2) with the capability of forming periodic nanostructures as the donor and a soluble fullerene (PC 70 BM) as the acceptor. The surface morphology of the blend film shows that the F8T2 and PC 70 BM phases are separated into large islands, which grow in size with increasing fraction of PC 70 BM. The power conversion efficiencies (PCEs) of the cells exhibit a distinct maximum as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…In this work we have synthesized a series of the novel homologous derivatives, C n -7 (n = 6, 8, 10), C n -8 (n = 6, 8, 10), 9a~e and 3a~e by using the same synthetic route. The terminally brominated n-alkanol derivatives 7 (C n -7: n = 6, 8,10,12) were prepared from the corresponding terminally dihydroxysubstituted n-alkanes. The phthalonitrile derivatives 8 (C n -8: n = 6, 8, 10, 12) were obtained from the terminally brominated n-alkanol derivatives 7 and commercially available 4-hydroxyphthalonitrile.…”
Section: -1 Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we have synthesized a series of the novel homologous derivatives, C n -7 (n = 6, 8, 10), C n -8 (n = 6, 8, 10), 9a~e and 3a~e by using the same synthetic route. The terminally brominated n-alkanol derivatives 7 (C n -7: n = 6, 8,10,12) were prepared from the corresponding terminally dihydroxysubstituted n-alkanes. The phthalonitrile derivatives 8 (C n -8: n = 6, 8, 10, 12) were obtained from the terminally brominated n-alkanol derivatives 7 and commercially available 4-hydroxyphthalonitrile.…”
Section: -1 Synthesismentioning
confidence: 99%
“…In this work, we have, therefore, synthesized a homologous series of the phthalocyanine-fullerene dyads, C nPcM(OFbaC60) (n=6,8,10,12; M=Cu, Ni, Co: 3a~f in Scheme 1), to obtain homeotropic alignment at rt and investigate the effects of spacer chain length (n=6, 8,10,12) and central metal (M=Cu, Ni, Co) on their mesomorphism. Very interestingly, each of the Pc-C 60 dyads 3a~e shows perfect homeotropic alignment for the columnar mesophases at rt.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they revealed that the dyad shows a smectic A phase. Liquid crystalline donor-acceptor block copolymers have been also used for photovoltaic applications [5][6][7][8][9][10][11][12]. Morphologies of the vertically oriented mesophase of D-A separated block copolymers are very favorable for organic photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
“…They can greatly reduce their costs to manufacture the solar cells. Liquid crystalline D-A systems are braodly classified into three groups: smectic liquid crystals [1][2][3][4], liquid crystalline copolymers [5][6][7][8][9][10][11][12] and discotic columnar liquid crystals [13][14][15][16][17][18][19][20][21][22][23][24][25]. In 2004 Kim et al reported that an organic photovoltaic cell was fabricated by using liquid crystalline N,N'-diheptyl-3,4,9,10-perylenetetracarboxylicdiimide (PTCDI-C7) as the electron acceptor and zinc phthalocyanine (ZnPc) as the electron donor [1].…”
Section: Introductionmentioning
confidence: 99%
“…Relationship between photovoltaic properties and charge dynamics in nanophase-separated F8T2/PCBM blend has been investigated. The F8T2 and PC 70BM blends maintained the phase separation into large islands, which formed percolated pathways for electron and hole-transport with charge separation at the interface between F8T2 and PC70BM, when annealed at temperature near the phase transition [13]. The device characteristics of F8T2 film on thick porous TiO2 substrates of different morphology as a function of device design have been studied.…”
Section: Introductionmentioning
confidence: 99%